Gasdermin D‐Mediated Pyroptosis Exerts Two Opposite Effects of Resisting Enzymatic Digestion and Expanding Inflammatory Response in Acute Pancreatitis - Chaoxu Liu; Ning Liang; Chen Wu; Zhaoyan Qiu; Qian Huang; Xiaolong Wei; Shurong Zhang; Shuanghong Lei; Tao Yang; Gang Wang; Qian Wang (Advanced Science)
Abstract Gasdermin D (GSDMD)‐induced pyroptosis is associated with inflammatory disease. However, the role of GSDMD in acute pancreatitis (AP) is not yet fully elucidated. This study reveals that GSDMD serves two distinct functions in pancreatic acinar cells and macrophages. In acinar cells, GSDMD inhibits the synthesis of pancreatic enzyme by downregulating the expression of Prss1, Pnlip, and Amy1 via the inhibition of the protein kinase B (AKT)/mammalian target of rapamycin (mTOR)/ribosomal protein S6 (RPS6)/eukaryotic translation initiation factor 4E‐binding protein 1 (4EBP1) pathway. Moreover, GSDMD induces pancreatic acinar cells to express mucin 1 (MUC1) by activating the nuclear factor kappa‐B (NF‐κB) pathway, which forms a barrier that prevents digestive enzyme‐mediated digestion. However, GSDMD promotes the secretion of inflammatory cytokines by macrophages during AP. In addition, GSDMD increases the infiltration of macrophages and neutrophils in AP and increases the proportion of Th1 and Th17 lymphocyte subsets in peripheral blood. However, in general, the harmful effect of GSDMD in AP outweighs its beneficial effect, and GSDMD knockout can effectively alleviate AP. These findings indicate that GSDMD may be a potential target for the treatment of AP; however, its dual effects need to be comprehensively considered.